2012
DOI: 10.1083/jcb.201112135
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic position is a major determinant of presynaptic strength

Abstract: Positional information, independent of neuronal activity, regulates presynaptic strength, with the strongest presynaptic terminals closest to the soma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
(110 reference statements)
2
22
0
Order By: Relevance
“…Besides we found that the soma has absolutely the larger synapses with the larger recycling pool and the higher spontaneous release, but if spontaneous and evoked turnover is normalized on the size of the synapse, the relative release is higher at the processes. Recent publications found a distance from soma dependency of synapse size and evoked release at the processes [20,21]. In accordance with evoked release [21], spontaneous release declined along the processes with increasing distance to the soma (Additional file 1: Figure S5A), but remained constant, if spontaneous release was normalized on synapse size (Additional file 1: Figure S5B).…”
Section: Conclusion and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Besides we found that the soma has absolutely the larger synapses with the larger recycling pool and the higher spontaneous release, but if spontaneous and evoked turnover is normalized on the size of the synapse, the relative release is higher at the processes. Recent publications found a distance from soma dependency of synapse size and evoked release at the processes [20,21]. In accordance with evoked release [21], spontaneous release declined along the processes with increasing distance to the soma (Additional file 1: Figure S5A), but remained constant, if spontaneous release was normalized on synapse size (Additional file 1: Figure S5B).…”
Section: Conclusion and Discussionsupporting
confidence: 66%
“…Recent publications found a distance from soma dependency of synapse size and evoked release at the processes [20,21]. In accordance with evoked release [21], spontaneous release declined along the processes with increasing distance to the soma (Additional file 1: Figure S5A), but remained constant, if spontaneous release was normalized on synapse size (Additional file 1: Figure S5B). Our functional measurements indicated, that both forms of release exhibit the same relationship regarding distance from the soma with smaller, but more effective synapses at the process [11].…”
Section: Conclusion and Discussionsupporting
confidence: 66%
“…The integration of presynaptic and postsynaptic events is strongly influenced by their location along the dendritic arbor. Postsynaptic elements at distal synapses have the highest gain for integration, while presynaptic elements located at the distal end have the least gain (de Jong et al, 2012), thus the length of the dendritic arbor is critical for signal integration. Dendritic functional roles are also critical in the storage of long-term memory (Govindarajan et al, 2011).…”
Section: Dendritic Structure and Functionmentioning
confidence: 99%
“…Cultures were fixed at 14 DIV with 4% (vol/vol) formaldehyde and stained as described previously (49). Primary antibodies and dilution used: chicken anti-MAP (1:10,000; Abcam), guinea pig anti-vGlut1 (1:5,000; Millipore), and rabbit anti-synaptotagmin-1 (1:2,000; W855; a gift from T. C. Sudhof, Stanford University).…”
Section: Methodsmentioning
confidence: 99%